Politik legislasi Menentukan DeMokrasi (analisis Putusan no. 15/Puu-iX/2011) - Abdul Wahid (The Constitutional Court of the Republic of Indonesia, 2012)
Not all juridical products are along with the society’s aspiration. There are some of the juridical products assessed as against the democracy enforcement by the society. The verdict number 15/PUU-IX/2011 given by the Constitutional Court is a kind of correction to the performance of the lawmakers (UU) if the law they produce are considered contra-democracy. Besides, the verdict of the Constitutional Court to some of the articles in the Law No. 2 Year 2011 actually might be read as a warning from the Constitutional Court to the lawmakers, especially those regulating the problem of political parties so that their performance could be maximized and transparent, and consider egalitarianism in the future.